ADDITIONAL MODIFIED SCAPULAR STABILIZATION INTERVENTION IS BETTER THAN SHOULDER STRENGTHENING IN PECTORALIS MINOR STRETCHING TO IMPROVING SCAPULAR ALIGNMENT IN TAILORS WITH ROUNDED SHOULDER POSTURE - Adyasputri, A.A Istri Ayesa Febrinia; Tirtayasa, Ketut; Wahyuddin, Wahyuddin; Adiputra, Luh Made Indah Sri Handari; Widianti, I Gusti Ayu; Juhanna, Indira Vidiari (Sport and Fitness Journal, 2024)
Rounded shoulder posture is maladaptive posture with characteristic of shoulder protraction, downward rotation, and elevation with an increase in upper thoracic kyphosis. The purpose of this study was to prove that the addition of the modified scapular stabilization intervention was better than shoulder strengthening in pectoralis minor stretching to improve scapular alignment in tailors with rounded shoulder posture. This study is a true experiment study with pre and post test design. The study subject amounted to 24 people who were divided into two groups by simple random sampling. Experimental Group with modified scapular stabilization and pectoralis minor stretching and Control Group with shoulder strengthening and pectoralis minor stretching. Measurements were taken before and after intervention. Scapular alignment was measured using a L-squre ruler. In Experimental Group, pre-test mean 6.32±0.52 and post right scapular alignment was 4.83±0.57, with p value p<0.001 and pre-test mean 5.92±0.56 and post left scapular alignment was 4.61±0.52, with p value p<0.001 while in Control Group pre-test was found to be 6.27±0.58 and post right scapular alignment was 5.22±0.64  with p value p<0.001 and pre-test mean 5.81±0.77 and post left scapular alignment was 4.79±0.90, with p value p<0.001. This indicated that there was a significant difference in the decrease in scapular alignment before and after the intervention, followed by a different test for the right scapular alignment p=0,014 and left scapular p=0.029. The result there was a significant difference in the improvement of scapular alignment in the two groups. In conclusion, the intervention of modified scapular stabilization was better in improving scapular alignment than the shoulder strengthening intervention in tailors with rounded shoulder posture. Keywords: Modified Scapular Stabilization, Shoulder Strengthening, Scapular Alignment